2017
DOI: 10.18488/journal.82.2017.43.20.27
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low Oil Prices on the Trade Balance of Balkan Countries and their Energy Security

Abstract: Article History KeywordsCrude oil prices Trade balance Balkan Energy security Natural gas. F1, F4, Q3, Q4. This chapter examines the impact of low oil prices in the last years on the trade balance of Balkan countries and their energy security. The development of oil prices in the last years has a potential impact on all economies. Indeed the impact was positive for crude oil importing economies but in the other hand, negative impact on crude oil exporting economies. According to our analysis, the impact was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the article we have actively used the data and the findings of the paper by Vlahinić and Rosanda (2014), but we renewed the statistical data and added data on consumption and production of energy. The article by Obadi et al (2017) served as a proof to our opinion, that the prices of oil are less significant for the economies of the countries, except for Serbia, than the growth of consumption of energy resources. In this context, the alternative energy development looks as the best option.…”
Section: Literature Reviewmentioning
confidence: 92%
“…In the article we have actively used the data and the findings of the paper by Vlahinić and Rosanda (2014), but we renewed the statistical data and added data on consumption and production of energy. The article by Obadi et al (2017) served as a proof to our opinion, that the prices of oil are less significant for the economies of the countries, except for Serbia, than the growth of consumption of energy resources. In this context, the alternative energy development looks as the best option.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Few studies have directly dealt with the effects of oil prices on energy security (Obadi et al , 2017), but given that energy security of countries is affected by energy consumption and energy prices cost-effectiveness. The effects of oil prices on energy security and energy consumption are discussed below.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to studies, only Obadi et al (2017) studied the effect of oil prices on the trade balance and energy security in the Balkans. The results showed that low oil prices had a positive effect on energy security in crude oil-importing economies, but on the other hand had a negative effect on crude oil exporting economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The global competitive market encourages improving their performances, capabilities, and competencies in the marketplace to distinguish themselves from the competitors. Furthermore, innovation is an important key factor in achieving high business growth, entering new markets and increasing market share and in attaining competitive advantage (Ceptureanu, 2015;Obadi, Kosir & Korcek 2017).…”
Section: Innovation and Its Importancementioning
confidence: 99%